Analisis Persepsi Etika Profesi Akuntan Publik dalam Praktik Audit - Aripin Aripin; Nurul Hasyikin; Ardiansyah Putra; Hendri Lala (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to understand public accountants’ ethical perceptions and experiences in audit practice using a qualitative phenomenological approach. In the public accounting profession, integrity, objectivity, and independence are fundamental principles often challenged by ethical dilemmas. Through in-depth interviews with seven public accountants in Indonesia, the study reveals that external pressures from clients, economic interests, and organizational culture significantly influence ethical decision-making. The findings indicate that while professional ethics are well understood in theory, their implementation in real-life situations can be hindered by complexity and ambiguity. A strong ethical culture and transparent internal support systems help auditors maintain integrity. This research highlights the importance of continuous ethics training and the reinforcement of individual moral values in shaping a resilient and ethically sound public accounting profession.